Pengaruh Pendapatan dan Lingkungan Sosial Terhadap Keputusan Pembelian Secara Taqsith - Hartini, Kustin; Inggriani, Inggriani (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2020)
Income and social environment are factors that can influence purchasing decisions. The purpose of this study was to determine the effect of income and social environment on purchasing decisions in taqsith. This type of research with a quantitative approach. The sampling technique uses a purposive sampling technique with a total sample of 66 people. The data analysis method uses multiple linear analysis with the help of SPSS. From the results of the T Test and F Test show that partially income variables significantly influence the purchase decision taqsith with a probability value (Sig) 0.017 < (α) 0.05. Social environment variables also have a significant effect on taqsith purchasing decisions with a probability value (Sig) 0.033 < (α) 0.05. Simultaneously income and social environment significantly influence the purchase decision in taqsith and this can be seen from the probability value (Sig) 0,000 < (α) 0.05.